2006
DOI: 10.1021/la060491m
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Biomolecular Architectures and Self-Assembled Monolayers Based on a Cyclodecapeptide Regioselectively Addressable Functional Template

Abstract: A nanometer scale redox active biomolecular architecture has been successfully synthesized through an efficient chemoselective oxime based coupling between ferrocenyl groups and a regioselectively addressable cyclodecapeptide. This molecular tool exhibits electronic, structural, and chemical properties driven by the biomimetic recognition activity of the polypeptide skeleton associated to the well-defined electrochemical activity of metallocenyl probes. Biomolecular materials obtained by confinement of the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…4). The increase of the Fc number in the stem-loop structure is associated with a logarithmic decrease of the E which tends to the theoretical value of 58 mV corresponding to a reversible redox system [11]. This improvement of system reversibility could be correlated to the thermodynamic study described previously that revealed a better stability of the hairpin structure for ODNs modified with a higher number of Ferrocenes (Table 1).…”
Section: Electrochemical Study Of Fc-odnsupporting
confidence: 76%
“…4). The increase of the Fc number in the stem-loop structure is associated with a logarithmic decrease of the E which tends to the theoretical value of 58 mV corresponding to a reversible redox system [11]. This improvement of system reversibility could be correlated to the thermodynamic study described previously that revealed a better stability of the hairpin structure for ODNs modified with a higher number of Ferrocenes (Table 1).…”
Section: Electrochemical Study Of Fc-odnsupporting
confidence: 76%
“…Ferrocenyl groups were attached to a cyclodecapeptide (designed for anion sensing) and immobilized on a gold electrode [359]. Using CV, the Laviron method was applied only to the cathodic branch of the E p vs. υ plot (only for overpotentials higher than 0.1 V) as the anodic wave became indistinguishable at scan rates > 100V/s.…”
Section: Bridge and Diluentmentioning
confidence: 99%
“…37,38 Interestingly, they have also been used for the design of a nanometer scale redox active biomolecular architecture by using ferrocenyl units. 39 In this work we provide a comprehensive study of (i) the specic binding, (ii) the inuence of the residence time (i.e. contact time), and (iii) the inuence of the retraction rate on the hostguest rupture forces between a cyclodecapeptide scaffold bearing a monovalent or a tetravalent adamantyl (guest) group and two types of b-CD (host) covered substrates.…”
Section: Introductionmentioning
confidence: 99%